2019
DOI: 10.1111/aji.13203
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast‐derived CXCL12 promotes CD56brightCD82CD29+ NK cell enrichment in the decidua

Abstract: Problem: Decidual natural killer (dNK) cells play key roles in maternal-fetal immune regulation, trophoblast invasion, and vascular remodeling, and most dNK cell populations are CD56 bright CD16 − NK cells. However, the enrichment and redistribution of dNK cells in the local decidua have not been clarified yet. Method of study:A total of 45 women with normal pregnancies and 8 unexplained recurrent spontaneous abortion (RSA) patients were included. We isolated primary human dNK (n = 53) and peripheral blood NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 69 publications
(136 reference statements)
1
8
0
Order By: Relevance
“…Our previous studies have elucidated that CD82 in decidua plays many biological functions. For example, CD82 in DSCs is involved in controlling invasiveness of extravillous trophoblast (Li et al 2010), and CD82 in NK cells participates in the regulation of cell adhesion and residence in decidua during early pregnancy (Lu et al 2020). Based on this study and previous reports, we conclude that a higher level of CD82 under a positive regulation of COX-2/PGE2 promotes decidualization in vitro.…”
Section: High Intracellular Camp and Pge2 Concentrationssupporting
confidence: 74%
See 1 more Smart Citation
“…Our previous studies have elucidated that CD82 in decidua plays many biological functions. For example, CD82 in DSCs is involved in controlling invasiveness of extravillous trophoblast (Li et al 2010), and CD82 in NK cells participates in the regulation of cell adhesion and residence in decidua during early pregnancy (Lu et al 2020). Based on this study and previous reports, we conclude that a higher level of CD82 under a positive regulation of COX-2/PGE2 promotes decidualization in vitro.…”
Section: High Intracellular Camp and Pge2 Concentrationssupporting
confidence: 74%
“…It acts as a key regulator in limiting the inappropriate invasion of trophoblasts during decidualization (Li et al 2010, Gellersen et al 2013 and inhibiting tumor cell migration and metastasis (Liu et al 2021, Ma et al 2021. Additionally, CD82 is involved in the regulation of infiltration and adhesion of decidual NK cells during early pregnancy (Lu et al 2020). However, little is known about the specific mechanism of the upregulation of CD82 in decidua and its effect on decidualization.…”
Section: Introductionmentioning
confidence: 99%
“…Here we observed that the autophagy level of pNK cells was much lower than that of dNK, it is noteworthy that autophagy does not seem to be directly involved in the regulation of NK cell adhesion and cytotoxic activity. Along with blastocyst implantation, it is widely recognized that embryonic trophoblast cells secrete large amounts of CXCL12 at the maternal-fetal interface, which recruit and promotes the adhesion ability of NCAM1 brigh NK cells to DSCs in a CD82/ITGB1-dependetnt manner [37,38]. In this study, we found that decidualization was accompanied with the increase of autophagy, which might be due to the positive role of a significant increase in progesterone during early pregnancy [34].…”
Section: Discussionmentioning
confidence: 50%
“…CD56-bright NK cells only, and not the CD56dim subset, display CD117 (c-Kit) expression, high affinity receptor for IL-2 and CCR7 on their surface and express a higher level of CXCR3 (173). The CD56 bright NK cells are more potent producers of the following cytokines: IFN gamma, TNF alpha, GM-CSF, IL10, IL13.…”
Section: The Essential Role Of Cd56 In Development Of Cns Leukemiamentioning
confidence: 99%